1984
DOI: 10.1902/jop.1984.55.9.505
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal Treatment Without Maintenance: A Retrospective Study in 44 Patients

Abstract: This study presents our findings on 44 patients who were treated for periodontal disease and for varying reasons elected not to participate in the maintenance aspect of periodontal care. All patients were initially given intensive instructions in personal oral hygiene, along with initial scaling and root planing. Each patient had two or more quadrants of pocket reduction therapy. Tooth mortality revealed a mean annual adjusted tooth loss rate of 0.22 (4.7%). Between examinations, breakdown in the health status… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
191
2
8

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 225 publications
(212 citation statements)
references
References 15 publications
11
191
2
8
Order By: Relevance
“…These results suggest that patient motivation to seek treatment was important in determining adherence to instructions. This supports the findings of a previous study (8), which found that people with a positive self-image had better SPT compliance.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results suggest that patient motivation to seek treatment was important in determining adherence to instructions. This supports the findings of a previous study (8), which found that people with a positive self-image had better SPT compliance.…”
Section: Discussionsupporting
confidence: 92%
“…Economic and psychological factors may at least partially explain differences in compliance (7)(8)(9). Other factors are lack of satisfaction (10), fear of dental treatment, cost, socioeconomic status (SES) (7,11,12), age, sex, type of periodontal therapy, and cultural and geographic characteristics (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…43,44 Thorough and dedicated oral hygiene measures are arguably This is a classic case of severe generalised chronic periodontitis. Using the 2 × 2 tables we can see this patient has a risk of periodontal disease.…”
Section: Patient Compliancementioning
confidence: 99%
“…14,15 During maintenance therapy, sites may [16][17][18] Diode laser-assisted periodontal therapy using photodynamic therapy was not superior to conventional mechanical debridement, 19 however photodynamic therapy was shown to be superior in eliminating pockets especially in single rooted teeth maintenance phase as seen by Campos et al 20 In our study, piezoelectric ultrasonic unit (EMS) was used to perform SRP. Chapper et al found that there was no significant difference found in treatment outcomes of ultrasonic scaling alone or ultrasonic scaling followed by hand scaling as the final step.…”
Section: Discussionmentioning
confidence: 67%